The Full Multi: An open-source framework for modelling the transport and fate of nano- and microplastics in aquatic systems. (February 2022) - Domercq, Prado; Praetorius, Antonia; MacLeod, Matthew
Abstract: We present a freely available open-source modelling framework to explore environmental transport and fate of nano-and microplastics in aquatic systems. The "Full Multi" models 1) fragmentation of plastic into a predefined set of size classes, 2) speciation of plastic particles between pristine, heteroaggregated, biofouled, and biofouled & heteroaggregated species, 3) dynamic vertical exchange between water layers and sediment of a freshwater system, and 4) horizontal particle transport by eddy diffusion and advective flow. The Full Multi framework relates emission rates to environmental exposure concentrations while considering the intrinsic properties of plastic particles and variable environmental system properties. The model can be applied to analyse scenarios with different process descriptions, plastic types, emission routes and environmental parameters for hypothesis generation, to identify dominant fate processes, and in hazard and risk assessment. Here, we introduce and illustrate the framework by modelling plastic particles with a range of densities in a generic flowing river system. Graphical abstract: Image 1 Highlights: A new modelling framework for nano- and microplastics transport and fate in aquatic systems is presented. The framework represents multiple environmental compartments, plastic sizes and species. The Full Multi is a modular, easy-to-run and open-access model. Research prioritization is supported by hypothesis generation and scenario analysis. An illustrative example of the framework applied to three plastic types is provided.